2017
DOI: 10.3732/ajb.1700142
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of extracellular DNA released during border cell separation from the root cap

Abstract: DNA is an integral component of border cell extracellular traps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 56 publications
0
34
0
1
Order By: Relevance
“…Extensin macromolecules could possibly interact through isodityrosine bonds – catalysed by peroxidases present in the RET secretions – thus forming a sort of physical barrier or scaffold template that reinforces the whole network (Castilleux et al , ). The scaffold could include other molecules such as xyloglucan and exDNA on which antimicrobial compounds could assemble in a rapid‐response system to pathogen infection (Wen et al , ; Ropitaux et al , ).…”
Section: Rets and Nets Form From Pre‐existing Tissue And Organ Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensin macromolecules could possibly interact through isodityrosine bonds – catalysed by peroxidases present in the RET secretions – thus forming a sort of physical barrier or scaffold template that reinforces the whole network (Castilleux et al , ). The scaffold could include other molecules such as xyloglucan and exDNA on which antimicrobial compounds could assemble in a rapid‐response system to pathogen infection (Wen et al , ; Ropitaux et al , ).…”
Section: Rets and Nets Form From Pre‐existing Tissue And Organ Cellsmentioning
confidence: 99%
“…other molecules such as xyloglucan and exDNA on which antimicrobial compounds could assemble in a rapid-response system to pathogen infection (Wen et al, 2017;Ropitaux et al, 2019).…”
Section: Rets and Nets Form From Pre-existing Tissue And Organ Cmentioning
confidence: 99%
“…DNA-specific binding to metals has been studied in detail (Zhou et al, 2017), and understanding how exDNA-metal traps form and function could yield key insights into plant, animal, and soil health. As previously established, nuclease degradation of exDNA in border cell traps results in hampered trapping capacity of both abiotic and biotic stressors (Hawes et al, 2016a;Tran et al, 2016;Wen et al, 2017;Park et al, 2019). There is potential to improve agricultural pest management and remediation of contaminated sites through exploitation of this exDNA-based mechanism, perhaps by identifying specific DNA sequences that preferentially bind to metals and microbes.…”
Section: Discussionmentioning
confidence: 94%
“…Previously known as "sloughed root cap cells" (Knudson, 1919) based on the premise that they die and fall off, border cells are now known to function in protection of the growing root tip by a newly recognized immune response first identified in mammalian systems (Brinkmann et al, 2004). Like neutrophils, metabolically active border cells export extracellular DNA (exDNA)-based traps that protect root tips by immobilizing pathogens and thereby preventing infection (Hawes et al, 2012(Hawes et al, , 2016aWen et al, 2017). Genes encoding extracellular DNases (exDNases), which degrade exDNA, facilitate virulence of bacterial and fungal pathogens in both mammalian and plant systems (Buchanan et al, 2006;McCormick et al, 2010;Tran et al, 2016;Park et al, 2019).…”
mentioning
confidence: 99%
“…In 2016, these findings were supported by the results of Tran et al who showed that extracellular DNases from the plant pathogenic bacterium Ralstonia solanacearum degrade these extracellular traps and contribute to virulence [162]. Wen and coworkers showed that root tips of Zea mays display DNA-positive strands within 1 to 2 min after immersion in water [163]. The structures disappeared when treated with DNAse I [163].…”
Section: Extracellular Traps In Plantsmentioning
confidence: 87%